2017
DOI: 10.1016/j.cancergen.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free DNA mutation patterns in early and late stage colon and pancreatic cancer

Abstract: Cancer is a heterogeneous disease harboring diverse subclonal populations that can be discriminated by their DNA mutations. Environmental pressure selects subclones that ultimately drive disease progression and tumor relapse. Circulating cell-free DNA (ccfDNA) can be used to approximate the mutational makeup of cancer lesions and can serve as a marker for monitoring disease progression at the molecular level without the need for invasively acquired samples from primary or metastatic lesions. This potential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…The presence of the KRAS G12 mutation was associated with tumor responses observed on CT images in 76.9% of patients and provided the earliest measurement of treatment in 60%. Vietsch et al 62 analyzed the plasma of five PDAC patients at initial diagnosis with next-generation sequencing. An average of eight mutations was detected per sample, but concordance with the tumor sample was only 28%.…”
Section: Cfdna In Pancreatic Cancermentioning
confidence: 99%
“…The presence of the KRAS G12 mutation was associated with tumor responses observed on CT images in 76.9% of patients and provided the earliest measurement of treatment in 60%. Vietsch et al 62 analyzed the plasma of five PDAC patients at initial diagnosis with next-generation sequencing. An average of eight mutations was detected per sample, but concordance with the tumor sample was only 28%.…”
Section: Cfdna In Pancreatic Cancermentioning
confidence: 99%
“…Accumulating evidence demonstrated that genetic mutations are associated with the occurrence and prognosis of tumors (34)(35)(36), including HCC (37)(38)(39). In the present study, it was identified that mutations in miRNA-424 target genes were associated with biological features of HCC.…”
Section: Discussionmentioning
confidence: 48%
“…These mutations were within KRAS (n = 3), NRAS (n = 1), and BRAF (n = 1), and related to resistance of epidermal growth factor receptor blockade, which may contribute to chemotherapy selection. Some previous studies, including our own, reported that mutations not found in primary tumors could be detected in ccfDNA of CRC patients . However, detection of mutations in ctcDNA that were not found in primary tumors has only been reported in breast cancer patients .…”
Section: Discussionmentioning
confidence: 78%
“…Some previous studies, including our own, 2 reported that mutations not found in primary tumors could be detected in ccfDNA of CRC patients. 18,19 However, detection of mutations in ctcDNA that were not found in primary tumors has only been reported in breast cancer patients. 20,21 Recently, cancer has been considered to be a more heterogeneous disease than previously thought, 22 and discordance between primary and metastatic tumors has been reported.…”
Section: Discussionmentioning
confidence: 99%